Persepsi Guru MTsN 1 Lima Puluh Kota Tentang Asesmen Kompetensi Minimum - Teti Asmarni; Supratman Zakir (Arden Jaya Publisher, 2023)
The government, in this case the Ministry of Education and Culture as the organizer of education in Indonesia, always tries to make changes for the better. The writing of this article aims to analyze the perceptions of MTsN 1 Lima Puluh Kota teachers about the Minimum Competency Assessment (AKM). This research uses a survey method with descriptive qualitative research type. Data were obtained through interviews and documentation. The data obtained was analyzed by reducing the data by describing the results of the interview. The results showed that almost all teachers had a positive perception of the AKM. Some of the obstacles encountered during the implementation of the AKM and character survey came from the factor of students who were slow in operating computers and did not understand the meaning of questions with various types of questions. The obstacle on the teacher's side was the teacher's competence in assisting students to prepare for the AKM. The efforts of madrasah and teachers to complete infrastructure, train students to operate computers, train students with questions, habituation of madrasah literacy activities. The results showed that minimum competency assessment needs to be socialized to students and training for teachers. Keywords: Perception, Teachers, Minimum Competency Assessment (MCA)